Impact of V617F JAK2 Mutation on Monocyte Tissue Factor and Procoagulant Activity in Patients with Essential Thrombocythemia(ET) or Polycythemia VERA (PV) - Falanga, Anna; Vignoli, Alfonso; Marchetti, Marina; Russo, Laura; Panova-Noeva, Marina; Balducci, Donatella; Salmoiraghi, Silvia; Barbui, Tiziano; Cate, Hugo ten; Rambaldi, Alessandro (Blood, 2008)
Clinical data suggest an increased thrombotic risk in patients with ET or PV carrying the JAK2V617F mutation. Laboratory data from our group show that ET patients carrying the JAK2V617F mutation are characterized by an enhanced platelet and neutrophil activation status (Falanga et al, Exp Hem 2007) and blood coagulation activation (Marchetti et al, Blood 2008), as compared to JAK2 wild-type ET. Since monocytes significantly contribute to blood coagulation activation as an important source of circulating tissue factor (TF), in this study we aimed to characterize the prothrombotic phenotype of monocytes from ET and PV patients and to evaluate whether and to what extent it is influenced by the JAK2V617F mutation. Twenty-four ET patients (10 JAK2 wild-type; 14 JAK2V617F carriers with 2%–35% mutant allele burden), 27 PV patients (all JAK2V617F carriers, 16 with 9%– 44% and 11 with 60%–100% allele burden, respectively), and 20 age-matched healthy subjects (controls, C) were enrolled into the study. Monocyte-associated TF antigen was measured on the cell surface by whole blood flow-cytometry, in both basal condition and after in vitro stimulation by bacterial endotoxin (lypopolysaccharide, LPS), as well as in cell lysates by ELISA. Monocyte procoagulant activity was evaluated by the Calibrated Automated Thrombogram (CAT) as the capacity of isolated monocyte lysates to induce thrombin generation in normal pool plasma. In basal conditions, significantly (p<0.05) higher surface levels of TF were measured on monocytes from ET (17.1±3.2% positive cells) and PV (24.4±3.7% positive cells) patients compared to C (8.2±1.9% positive cells). Similarly, the total TF antigen content of cell lysates was significantly increased in patients compared to C. The analysis of the data according to JAK2V617F mutational status, showed a gradient of increased TF expression starting from JAK2V617F negative patients (11.7±2.5%), versus JAK2V617F ET and PV subjects with <50% allele burden (20.3±3.6% and 23.2±2.8%, respectively), versus JAK2V617F PV patients with >50% allele burden (26.1±4.2%). The in vitro LPS stimulation significantly increased TF expression on monocytes from all study subjects and C compared to non-stimulated monocytes (p<0.05 for all groups), with a more elevated expression by monocytes from PV and ET patients compared to C. However, the relative increase in TF expression was greater in C (=3.7 fold) compared to both ET (=2.2 fold) and PV (=2 fold) patients. As observed in basal conditions, LPS-induced TF was higher in JAK2V617F positive patients as compared to negative, with the highest expression in JAK2V617F PV carriers with >50% allele load. Thrombin generation induced by monocytes from ET and PV patients was significantly increased compared to controls, as determined by significantly higher thrombin peaks (ET=145±12, PV=142±17, C=72.2±5 nM), and quantity of thrombin generated in time, i.e. the endogenous thrombin potential (ETP) (ET=1143±34, PV=1074±64, C=787±58 nM*min). The JAK2V617F PV subjects with >50% allele burden presented with the highest thrombin generation capacity (peak= 184±34 nM; ETP= 1268±32 nM). Our data indicate that the expression of the JAK2V617F mutation in ET and PV patients may confer to monocytes a different hemostatic phenotype in terms of increased expression of surface TF and thrombin generation capacity. These findings are in agreement with the previous observation of a hypercoagulable state associated with this mutation and suggest a new mechanism linking hemostatic cellular phenotypic alteration to genetic dysfunction in patients with myeloproliferative disease.